Prospects of Boswellic Acids as Potential Pharmaceutics - Du, Zhiyong; Liu, Zhenli; Ning, Zhangchi; Liu, Yuanyan; Song, Zhiqian; Wang, Chun; Lu, Aiping (Planta Medica, 2015)
Boswellic acids have long been considered the main bioactive components of frankincense, and many studies in vitro and in animals as well as several clinical studies have confirmed their various bioactivities. In particular, a large number of mechanistic studies have confirmed their anti-inflammatory and antitumor activities. However, not every boswellic acid exhibits a satisfactory pharmacological performance, which depends on the chemical structure and functional groups of the acid. To enhance the pharmacological values of boswellic acids, derivatization has been specifically applied with the aim of discovering more active derivatives of BAs. In addition, the preliminary pharmacokinetic studies of these compounds using various standard methods show their poor bioavailability in humans and rodents, which has led to questions of their pharmacological relevance and potentially limits their use in clinical practice and pharmaceutical development. To improve these effects, some approaches have shown some improvements in effectiveness, and the new formula compatibility approach is considered a very reasonable method for improving the bioavailability of boswellic acids.
Keywords: Boswellia serrata; Burseraceae; boswellic acids; derivatization; pharmacokinetics; analysis methods; new formula